Degradation of unsymmetrical dimethylhydrazine in water by hybrid mesoporous TiO2 and H2O2 under vacuum ultraviolet (VUV) irradiation - Yuanzheng Huang (Elsevier, 2021)
In this study, mesoporous TiO2 with various hydrolysis rates were prepared and combined with H2O2 for the photodegradation of unsymmetrical dimethylhydrazine (UDMH) under VUV irradiation. Results showed that the mesoporous TiO2 synthesized by the hydrolysis in water (MT100) exhibited a good mesoporous structure and the largest specific surface area (178.85 m2 g−1). Consequently, MT100 showed the best degradation efficiency, with the rate constant (k) for VUV/MT100 and VUV/MT100/H2O2 of 0.0185 and 0.2595 min−1, respectively, which was 1.4 and 4.0 times of that of P25. The addition of H2O2 significantly enhanced the degradation efficiency by photoactivation of H2O2 and the synergistic effect. The rate constant and the mineralization rate (after a 3-h treatment) increased by 13 and 3.8 times when 40 mM H2O2 was added into VUV/MT100. The weak alkaline condition (pH = 9) would facilitate the degradation of UDMH. The ⋅OH was the key oxidizing species in VUV/MT100/H2O2. Eight intermediates were detected during the degradation and the possible pathways of UDMH degradation in VUV/MT100/H2O2 process were proposed. VUV/MT100/H2O2 provides an efficient method to degrade UDMH.